Green synthesis of MgO nanoparticles using Phyllanthus emblica for Evans blue degradation and antibacterial activity. (2022) - Ananda, A.; Ramakrishnappa, T.; Archana, S.; Reddy Yadav, L.S.; Shilpa, B.M.; Nagaraju, G.; Jayanna, B.K.
Graphical abstract: Abstract: The eco-friendly synthesis of nanomaterials utilizing plant extract has always been eco-sustainable and enticing. The present study reports the synthesis of MgO nanoparticles named MGN1, MGN2, MGN3, and MGN4 with different fuel ratios using the Phyllanthus emblica aqueous fruit juice popularly known as Indian gooseberry. The structure and size of MGN NPs were studied using techniques such as XRD, SEM, and TEM. The FTIR spectrum played a crucial role in showcasing the significant functional groups present in the MGN NPs, by showing the strong absorption in the range 424 cm −1 . Under UV light irradiations, photocatalytic degradation of Evans blue (EB) dye was investigated, and the result showed around 90% removal of the dye from the wastewater. Further, the same compound is assessed for antibacterial activity on several distinct pathogenic bacteria using the agar well diffusion technique: Pseudomonas aeruginosa (Gram-negative), Staphylococcus aureus (Gram-positive), Acinetobacter baumannii (Gram-negative), Escherichia coli (Gram-negative) and Klebsiella pneumoniae (Gram-negative).